Proof-of-concept evaluation of next-generation sequencing-based liquid biopsy for non-invasive cancer detection in cats - Ruiz-Perez, Carlos A.; Nakashe, Prachi; Marshall, Maggie A.; Marass, Francesco; Tang, Tuong; McLennan, Lisa M.; Kroll, Marissa; Flesner, Brian K.; Gray, Suzanne; Rafalko, Jill M.; Grosu, Daniel S.; Hicks, Susan C.; et al. (Frontiers in Veterinary Science, 2024)
This proof-of-concept evaluation demonstrates that next-generation sequencing-based liquid biopsy can detect genomic alterations in the blood of cats with cancer and the absence of such alterations in the blood of presumably cancer-free cats. Two cats with cytologically confirmed lymphoma and nine presumably cancer-free cats were included in this analysis. Whole blood was collected from each subject and samples were subjected to DNA extraction, library preparation, and next-generation sequencing. Both cancer-diagnosed subjects had somatic copy number variants (a “cancer signal”) identified in cell-free DNA, suggesting the current presence of cancer in these subjects. All nine presumably cancer-free subjects had unremarkable genomic profiles, suggesting the absence of cancer in these subjects. Liquid biopsy using next-generation sequencing of cell-free DNA allows for blood-based detection of cancer-associated genomic alterations in cats. Such technology has the potential to offer considerable utility in veterinary medicine, particularly for the non-invasive prioritization of small cell intestinal lymphoma versus inflammatory bowel disease in cats with gastrointestinal signs. This study lays the foundation for future studies to fully validate this type of testing for use in clinical practice.